Cita rasa khas kopi Topidi melalui proses panen hingga metode pengolahan dry process dan full wash - Mutiara, Mutiara; Rustam, Aswar; Nurindah, Nurindah (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2023)
There are three types of coffee that are commonly cultivated, namely arabica coffee (Coffea arabica), robusta coffee (Coffea robusta), and liberica coffee (Coffea liberica). Topidi is one of the largest C. arabica and C. robusta producing areas in South Sulawesi. Topidi coffee is known for its distinctive taste. Coffee processing methods that are widely used by the community are the dry process and full wash methods. Based on the results of field work practices, it was found that the distinctive taste of Topidi coffee comes from the consistency of farmers to a good level of maturity at harvest to processing. Only superior coffee will be processed, as well as the selection of the dry method to produce coffee with a full body, a variety of fruity flavors, low bitter and sour taste, and low caffeine content and meet the value of coffee quality standards powder